AUDIT MANAJEMEN ATAS PENGELOLAAN PIUTANG USAHA PADA PT. PELABUHAN INDONESIA IV (PERSERO) CABANG SAMARINDA - Muhammad Adhani Adhitaqwan Mardiana dan Camelia Verahastuti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
The purpose of this research is to know whether management audit implementation as financial function toward ship service accounts receivable management in PT. Pelabuhan Indonesia IV (Persero) Samarinda branch is effective. The analysis instrument was comparative method, this method was done by collecting and explaining non-numeric data (qualitative) and then it was compared with relevant theories to get result clarity which can be resulted as conclusion and suggestion. The result of the research analysis showed that management audit implementation as financial function toward ship service accounts receivable management in PT. Pelabuhan Indonesia IV (Persero) Samarinda branch was less effective. The conclusion of this research was there were some flaws in ship service accounts receivable management which needs to be fixed to improve company efficacy.